1994
DOI: 10.1161/01.atv.14.10.1553
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism and heterozygous familial hypercholesterolemia. Sex-specific effects.

Abstract: The impact of apolipoprotein (apo) E polymorphism on interindividual variation in plasma lipid, lipoprotein, and apolipoprotein levels was studied in a sample of familial hypercholesterolemic (FH) patients (147 women, 116 men) with the same mutation, a >10-kilobase deletion of the low-density lipoprotein (LDL) receptor gene. Each trait was adjusted for concomitants (age, age squared, height, weight, weight squared) for each sex separately before the apoE genotypic effects were estimated. The relative contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 55 publications
3
28
0
1
Order By: Relevance
“…This effect was not sex-specific. Ferrieres et al 7 showed a similar effect in French-Canadian FH women but not in men. Tonstad et al 16 did not detect any influence of apoE genotype on lipid levels of Norwegian FH children.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This effect was not sex-specific. Ferrieres et al 7 showed a similar effect in French-Canadian FH women but not in men. Tonstad et al 16 did not detect any influence of apoE genotype on lipid levels of Norwegian FH children.…”
Section: Discussionmentioning
confidence: 84%
“…6 In healthy adults, between 4% and 8% of the total variance in plasma LDL-C concentrations can be attributed to the common apoE polymorphism. 6,7 ApoB is the major apolipoprotein of chylomicrons, VLDL, IDL, LDL, and lipoprotein(a) particles. The apoB gene located on chromosome 2 has numerous polymorphic sites, among which are those due to an insertion (Ins) or a deletion (Del) of 9 base pairs, which produces a difference of 3 amino acids in the signal peptide (for reviews, see Humphries and Talmud 8 and Vedie et al 9 ).…”
mentioning
confidence: 99%
“…The possible influence of genetic factors other than variation at the LDLR gene locus could not be examined fully in this relatively small sample. Allelic variation in the genes for apoE, 28 apo(a), 29 angiotensin-converting enzyme, 30 and apoB 31 have been reported to affect lipoprotein concentrations and predisposition to premature CAD in subjects with FH, but these effects are relatively small. Data for the apo(a) and apoE phenotypes/genotypes were not available for the original Chinese FH patients, but it is unlikely that variation in these genes alone is a cause for the highly significant difference in phenotype observed in this study between the Chinese FH heterozygote cohorts of such similar racial origin.…”
Section: Discussionmentioning
confidence: 99%
“…28 APOE genotype alters lipoprotein particle distribution and number and triglyceride metabolism, and gender differences in these effects have been reported. 29,30 These observations suggest that the femalespecific protective effect of the APOE4 genotype on survival in CLL could relate to several mechanisms including modulation of CLL cell apoptosis by estrogen through the apoE/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%